Comparative Pharmacovigilance Analysis of Selected Cardiotoxicity Signals Associated with Doxorubicin and Epirubicin Based on EudraVigilance Data - Emilia Sorina Fiat; Anca Butuca; Carmen Maximiliana Dobrea; Steliana Ghibu; Razvan Constantin Vonica; Adina Frum; Claudiu Morgovan; Nastaca Alina Palade; Crina Cristina Solomon; Florina Batar; Bogdan Ioan Vintila; Maria Totan; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Anthracycline-induced cardiotoxicity may compromise cancer treatment and long-term outcomes. Although differences in the cardiotoxicity profile of epirubicin and doxorubicin have been reported, direct comparative pharmacovigilance evidence remains limited. This study compared their cardiovascular adverse reaction reporting profiles using EudraVigilance (EV) data. Methods: Aggregated Individual Case Safety Reports submitted up to 12 July 2026 on the European portal were analyzed. Descriptive analyses assessed demographic characteristics, report origin, reporter type, System Organ Class distribution, seriousness, and clinical outcomes. Cardiotoxicity-related preferred terms (PTs) were identified using the Standardized MedDRA Queries “Cardiac failure”, “Cardiomyopathy”, and “Myocardial infarction”. Comparative disproportionality analysis was restricted to reports submitted by healthcare professionals. Reporting odds ratios and 95% confidence intervals were calculated for PTs with at least five reports for each drug. Results: Overall, 52,257 reports for doxorubicin and 31,049 for epirubicin were identified. Cardiac disorders were reported in 4459 doxorubicin cases and 1406 epirubicin cases, with over 97% classified as serious. Among 51 cardiotoxicity-related PTs, doxorubicin showed significantly higher reporting odds for cardiogenic shock, congestive, chronic, acute, and left ventricular cardiac failure, decreased ejection fraction, cardiomyopathy, cardiotoxicity, toxic cardiomyopathy, acute myocardial infarction, myocardial infarction, and increased troponin. The strongest disproportionality signals were observed for cardiogenic shock, toxic cardiomyopathy, cardiomyopathy, and cardiotoxicity. Conclusions: Doxorubicin was associated with a more pronounced pattern of cardiotoxicity-related reporting and disproportionality signals than epirubicin in the EV database. These findings highlight potential differences in the cardiovascular safety profiles of the two anthracyclines and provide signals that warrant further investigation, while underscoring the importance of cardiovascular risk assessment and monitoring in patients receiving anthracycline therapy. However, disproportionality signals do not establish incidence, absolute risk, or causality and require confirmation in prospective comparative studies.